Morphology of the testes of animals during estrogen injection in the prenatal period - Sulaimanova Rimma; Kvochko Andrey; Askhabova Eliza (E3S Web of Conferences, 2023)
The aim of the study was to investigate the morphological changes in the testes of the offspring of white non-pedigreed laboratory mice when the synthetic oestrogen analogue synestrol was prenatally injected to the mother. After fertilization, the females were divided into 2 groups which received a single intramuscular injection of the synthetic oestrogen analogue synestrol on day E 11.5 of gestation at the same time of the day. The intact group was not exposed to any treatment. The experimental group was exposed to synestrol, a synthetic oestrogen analogue, as a 2% oil solution at a dose of 40 µg/kg (C-40). The results of morphometric analysis of testes of descendants of white outbred laboratory mice after prenatal single injection of synthetic oestrogen analogue synestrol in a dose of 40 µg/kg showed morphological changes in the organ parenchyma, manifested as decrease in mean number of Sertoli cells (C-40) 17.4±1.1 compared to intact group 20.8±1.9; decrease in mean number of spermatogonia (C-40) 24.4±1.1 compared to intact group, decrease in mean number of spermatozoa (C-40) 178.0±4.2 compared to intact group 196.6±5.3. There was observed a change in the endocrine apparatus of testes, expressed as a decrease in the mean area of Leydig cell nuclei in the intact group of 6,72±1,78. Prenatal effects of synestrol revealed in an experimental model, allow us to use it to search for means of postnatal developmental testicular dysfunction correction as well as to develop optimal doses of oestrogenic preparations during pregnancy.